Mentoring Paraphrasing and Translation Bilingual Scientific Articles to Students in Physics Education Study Program of IAIN Palangka Raya - Qamariah, Zaitun; Yuliani, Hadma (Society : Jurnal Pengabdian Masyarakat, 2024)
This community service is conducted to facilitate a mentoring program in paraphrasing and translating scientific works from Indonesian to English for students of the Physics Education Study Program at the State Islamic Institute (IAIN) of Palangka Raya. This initiative addresses the students' need to possess basic skills in paraphrasing and translating Indonesian to English, particularly in the form of academic works, to enhance their access to international scientific discourse. The activity is implemented through mentoring sessions focused on paraphrasing techniques, translation, linguistic nuances, and conventions of academic writing. This collaborative activity between lecturers and students aims to improve paraphrasing and translation skills to foster a deeper understanding of academic works among students. The outcomes of this activity are expected to contribute to the academic and professional development of students, preparing them with the ability to communicate their research findings on a global scale effectively. The paraphrasing and translation mentoring activities are expected to assist students in publishing scientific works in accredited national and international science journals.